Preliminary Archaeogeophysical Survey of the Construction Site in the Vicinity of the Narikala Citadel - Odilavadze, Davit T.; Chelidze, Tamaz L.; Yavolovskaya, Olga V. (Journals of Georgian Geophysical Society, 2025)
Due to the construction and rehabilitation works in the territory of “Old Tbilisi”, one of the historically ancient and archaeologically very important places in the capital of Georgia, Tbilisi, there was a need to carry out a preliminary reconnaissance archaeogeoradiolocation survey. The pre-marked area for the archaeogeoradiolocation survey was intended as a place for the operation of construction equipment. During the construction process, it was possible to damage multi-ton construction equipment and cause accidents as a result of underground voids, as well as destroy possible archaeological monuments. The archaeogeoradiolocation survey revealed a number of voids, signs of the presence of possible archaeological sites, and mapped their locations. The archaeogeoradiolocation work was performed using a Zond 12e georadar, the data was collected, processed and interpreted using the Prizm 2.6 software. The aim of the task was to conduct a georadiolocation survey to identify voids in the subsurface and near-surface areas. It turned out that the study area is loaded with objects containing cavities of various shapes and contents. The continentality of the soil is disturbed by numerous cavities. Their depth ranges from 0.5 m to 5 m and their length is 1-5 m. A boundary between geological layers has been identified, on which a radio image of a man-made object could be located, such as: a foundation, tunnel, culvert or other cylindrical object located above the foundation and with a width of 1–1.5 m. The presence of a geological object is not excluded. From an archaeological-geological point of view, the study requires further continuation of detailed archaeogeoradiolocation works.